A randomised controlled dismantling trial of sleep restriction therapies for chronic insomnia disorder in middle childhood: effects on sleep and anxiety, and possible contraindications. (17th June 2022) - Cain, Neralie; Richardson, Cele; Bartel, Kate; Whittall, Hannah; Reeks, Joseph; Gradisar, Michael
Summary: Sleep restriction therapies likely drive improvement in insomnia in middle childhood via increases in homeostatic sleep pressure (e.g., evening sleepiness). Increased evening sleepiness may also dampen comorbid anxiety symptoms; and reduced wakefulness in bed may reduce worry. However, sleep restriction therapies have never been evaluated as a standalone intervention in this population. The mechanism of action needs testing, as do effects on anxiety, and cognitive performance and parasomnias (possible contraindications). This randomised controlled trial evaluated the efficacy of two "doses" of sleep restriction therapy (sleep restriction therapy, bedtime restriction therapy), compared to a control condition (time in bed regularisation). A total of 61 children (mean [SD, range] age 9.1 [2.1, 6–14] years; 54% female) with chronic insomnia disorder received two weekly 60‐min treatment sessions with a psychologist. Sleep, sleepiness, anxiety, worry, cognitive performance, and parasomnias were measured pre‐treatment, across treatment, and at 4‐weeks post‐treatment. Both the sleep and bedtime restriction groups experienced reductions in total sleep time ( d = 1.38–2.27) and increases in evening sleepiness ( d = 1.01–1.47) during the 2‐week treatment, and improvements in insomnia (i.e., sleep onset latency; d = 1.10–1.21), relative to the control group. All groups reported improved anxiety and worry, yet there were no differences between the control and restriction groups (all p > 0.658). Time in bed increased at the 1‐month follow‐up, and benefits to sleep and insomnia were maintained. There were no adverse effects on cognitive functioning (all p > 0.259), nor parasomnia occurrence (all p > 0.740). These results suggest that sleep restriction therapies are brief, yet effective, standalone interventions for insomnia in middle childhood, and improvements are likely due to increased sleepiness, not sleep regularisation.